2021
DOI: 10.1186/s13063-021-05439-7
|View full text |Cite
|
Sign up to set email alerts
|

The Core Outcome DEvelopment for Carrier Screening (CODECS) study: protocol for development of a core outcome set

Abstract: Background Reproductive genetic carrier screening is a type of genetic testing available to those planning a pregnancy, or during their first trimester, to understand their risk of having a child with a severe genetic condition. There is a lack of consensus for ‘what to measure’ in studies on this intervention, leading to heterogeneity in choice of outcomes and methods of measurement. Such outcome heterogeneity has implications for the quality and comparability of these studies and has led to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Current practice recommendations supporting the offer of RGCS have instead relied on a consensus-based approach [ 1 – 3 ]. The Core Outcome Development for Carrier Screening (CODECS) Study aims to address this issue by developing a set of agreed outcomes in collaboration with key stakeholders including patients, health professionals, researchers and policy-makers; known as a core outcome set (COS) [ 4 ]. A COS is a minimum set of outcomes that should be measured and reported in all studies on a particular topic and can improve the overall quality, comparability and synthesis of research findings in a body of literature.…”
Section: Introductionmentioning
confidence: 99%
“…Current practice recommendations supporting the offer of RGCS have instead relied on a consensus-based approach [ 1 – 3 ]. The Core Outcome Development for Carrier Screening (CODECS) Study aims to address this issue by developing a set of agreed outcomes in collaboration with key stakeholders including patients, health professionals, researchers and policy-makers; known as a core outcome set (COS) [ 4 ]. A COS is a minimum set of outcomes that should be measured and reported in all studies on a particular topic and can improve the overall quality, comparability and synthesis of research findings in a body of literature.…”
Section: Introductionmentioning
confidence: 99%
“…There is no accepted standard for consensus thresholds in COS development, with most setting a threshold of greater than 70% of stakeholders rating an outcome as critically important 5. A slightly higher threshold of 75% has been favored by some authors12–14 to increase rigor in the final step and this was agreed by our steering committee for the third round. Lower thresholds were selected for the preceding rounds to allow outcomes to be appraised with the benefit of comments and voting from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Systematic reviews of outcomes used in genetic counseling research (Athens et al, 2017; Madlensky et al, 2017) and in evaluating clinical genetics services (Payne et al, 2008) have found a lack of standardization in the tools used for measuring outcomes. This limits the ability to compare findings across studies (Resta, 2019; Richardson et al, 2021).…”
Section: Current State Of Evaluating Healthcare Quality In Genetic Co...mentioning
confidence: 99%